Improving the Solubility and Bioavailability of Progesterone Cocrystals with Selected Carboxylic Acids - Jing Xiong; Dezhong Xu; Hui Zhang; Yan Shi; Xiangxiang Wu; Sicen Wang (MDPI AG, 2024)
Progesterone (PROG) is a natural steroid hormone with low solubility and high permeability that belongs to biopharmaceutics classification system class II. In this study, novel pharmaceutical cocrystals of PROG were successfully prepared by solvent evaporation or a liquid-assisted grinding process aimed at enhancing its solubility and bioavailability. The cocrystal formers selected based on crystal engineering principles were carboxylic acids, namely, 4-formylbenzeneboronic acid (BBA), isophthalic acid (IPA), and 3-nitrophthalic acid (NPA). The cocrystal structures were characterized using multiple techniques. Single-crystal X-ray diffraction results showed that the carbonyl group, acting as a hydrogen bond acceptor, was pivotal in the cocrystal network formation, with C-H···O interactions further stabilizing the crystals. The cocrystals exhibited improved solubility and dissolution profiles in vitro, with no significant changes in hygroscopicity. The parallel artificial membrane permeability assay (PAMPA) models indicated that the cocrystals retained PROG's high permeability. Pharmacokinetic studies in Sprague-Dawley rats revealed that all cocrystals increased PROG exposure, with AUC(0~∞) values for PROG-BBA, PROG-IPA, and PROG-NPA being 742.59, 1201.72 and 442.67 h·ng·mL−1, respectively. These values are substantially higher compared to free PROG, which had an AUC(0~∞) of 301.48 h·ng·mL−1. Notably, PROG-IPA provided the highest AUC improvement, indicating a significant enhancement in bioavailability. Collectively, the study concludes that the cocrystal approach is a valuable strategy for optimizing the physicochemical properties and oral bioavailability of PROG, with potential implications for the development of other poor water-soluble drugs.